Strain engineering for controlled growth of thin-film FeNi L10. (1st February 2017) - Frisk, Andreas; Hase, Thomas P A; Svedlindh, Peter; Johansson, Erik; Andersson, Gabriella
Abstract: FeNi thin films in the L10 phase were successfully grown by magnetron sputtering on HF-etched Si ( 0   0   1 ) substrates on Cu/Cu100− x Ni x buffers. The strain of the FeNi layer, ( c / a ) F e N i, was varied in a controlled manner by changing the Ni content of the Cu100− x Ni x buffer layer from x = 0   a t . % to x = 90   a t . %, which influenced the common in-plane lattice parameter of the CuNi and FeNi layers. The presence of the L10 phase was confirmed by resonant x-ray diffraction measurements at various positions in reciprocal space. The uniaxial magnetocrystalline anisotropy energy K U is observed to be smaller (around 0.35 MJ m −3 ) than predicted for a perfect FeNi L10 sample, but it is larger than for previously studied films. No notable variation in K U with strain state ( c / a ) F e N i is observed in the range achieved ( 0.99 ≲ ( c / a ) F e N i ≲ 1.02 ), which is in agreement with theoretical predictions.